A BIG DATA AND IT’S SECURITY CHALLENGE IN DIGITAL MEDIA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research work discuss about the big data and related problem. In the current generation big dataplay’s an important role in various data mining application. This research work discuss the various field in whichapply big data application. There are many critical issues and challenges face in the big data. Big DataDuplication is one of the challenging problem between researchers. In the last decade the growth of big dataexponentiation, Terabytes, Petabyte, Exabyte, Zettabyte bytes data generated in every day in a single stockmarket research application. In this process huge amount of decapitate data also generated in Terabytes as wellas Petabytes. Similar that social media application generated large amount of duplicate information. In thisresearch work focus on different problems and hurdles of big data and its related issues.However, encryptedinformation introduce new challenges for cloud information de-duplication that becomes crucial for giantinformation storage and process in cloud. De-duplication schemes cannot work on encrypted information.Existing solutions of encrypted information de-duplication suffer from security weakness. They cannot flexiblysupport information access management [13] and revocation. Therefore, few of them is pronto deployed inobserve. During this paper, we propose a theme to de-duplicate encrypted information hold on in cloudsupported possession challenge and proxy re-encryption. It integrates cloud information de-duplication withaccess management.